Coves of departure : field notes from the Sea of Cortez - Farnsworth, John Seibert (Comstock Publishing Associates, an imprint of Cornell University Press, 2018)
"The author documents ten years of explorations of the Baja peninsula and the Sea of Cortez as a professor taking undergraduates on sea kayak expeditions to the Isla Espiritu Santo archipelago. He also tells of his experiences with a condor restoration project in the Sierra San Pedro Martir based in a field station on Bahia de los Angeles"--